Effects of two isometric strength training methods on jump and sprint performances: a randomized controlled trial - Lum, Danny (2021)
Isometric strength training (IST) with rapid non-sustained contraction (RIST) is effective in improving the ability to generate force rapidly. However, the neuromuscular adaptation of IST with sustained contraction (SIST) and RIST is not known. Therefore, the aim of the study was to compare the neuromuscular adaptations of RIST with SIST. Methods Thirty-three national floorball players (23.9 ± 3.1 years old; 1.69 ± 0.08 m; 64.6 ± 11.1 kg) were recruited for this study. Pre- and post-test included countermovement jump (CMJ), 30-m sprint (TT30), isometric squat at 90° (ISqT90) and 120° (ISqT120) knee angles. They were randomly assigned to either control (Con) (n = 9), RIST (n = 12) or SIST (n = 12) group and performed 12 sessions of intervention training. All groups performed the same sets of exercises, but RIST and SIST had to perform ISqT with and without sustained contraction, respectively. Results Time × group effect for CMJ height (P = 0.01, ƞp 2 = 0.25), peak force (PF) (P = 0.03, ƞp 2 = 0.22) and rate of force development (RFD) (P = 0.02, ƞp 2 = 0.22) obtained from ISqT120 were noted. A main effect for time was observed in CMJ height, PF obtained from ISqT90 and ISqT120, and RFD obtained from ISqT90 (P < 0.01, 0.27 < ƞp 2 < 0.57). There was greater improvement in TT30 (P = 0.043, d = 3.00), ISqT90 PF (P = 0.034, d = 3.12), ISqT120 PF (P = 0.003, d = 4.54) and ISqT120 RFD (P = 0.033, d = 1.36) in the SIST than the Con group. Conclusion SIST was more effective in improving strength and dynamic performance as compared to RIST, making it a viable training method to enhance dynamic performances.